Application of plant growth-promoting rhizobacteria to control Papaya ringspot virus and Tomato chlorotic spot virus. (21st July 2017) - Abdalla, Osama A.; Bibi, Shagufta; Zhang, Shouan
Abstract: Papaya ringspot virus (PRSV-W) and Tomato chlorotic spot virus (TCSV) are responsible for severe losses in cucurbits and tomato production in south Florida and other regions in the USA. Traditional chemicals are not effective to control these viruses. Using plant growth-promoting rhizobacteria (PGPR) may present an alternative to control these viruses. Results from this study demonstrated that applying mixtures of PGPR strains is more efficient to control PRSV-W and TCSV compared to individual PGPR strain only. The application method significantly affected the efficiency of PGPR to control PRSV-W and TCSV. The highest reduction in disease severity of both PRSV-W and TCSV occurred in case of soil drenching with PGPR, followed by root dipping and seed coating treatments. Application of PGPR mixtures of (IN937a & SE34) or (IN937a &, SE34 & T4) were the most efficient methods to control these viral diseases.